A resin cement slurry for cementing and its preparation method and application

CN117865578BActive Publication Date: 2026-10-30CHINA OILFIELD SERVICES LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410052964.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-12
Publication Date
2026-10-30
Estimated Expiration
2044-01-12

AI Technical Summary

Technical Problem

虽然环氧树脂改性固井水泥石,通过降低水泥石渗透性和改善水泥石力学性能,有助于水泥石长期完整性,但是在现有环氧树脂改性技术中,仍存在一些不足或需改进的地方

Benefits of technology

[0024](1)本发明通过将含有铝粉的油性树脂浆液与水性水泥浆按一定体积比混合,利用水泥浆中相容剂,实现树脂液在水泥浆中“原位乳化”(In situ emulsification),操作过程简单,采用现有设备即可实现现场施工;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117865578B_ABST
    Figure CN117865578B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of oilfield cementing, and particularly relates to a resin cement slurry for cementing, a preparation method and application thereof. The resin cement slurry for cementing comprises resin slurry and cement slurry in a volume ratio of 0.5:9.5 to 9.5:0.5. The resin cement slurry technology meets the basic performance requirements of cement slurry for cementing engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oilfield cementing technology, specifically relating to a resin cement slurry for cementing, its preparation method, and its application. Background Technology

[0002] The purpose of cementing is to provide effective isolation between formations and to ensure the integrity of the wellbore seal. It is recognized that gas channeling during cement slurry setting, as well as stress and thermal shock damage to the cement sheath due to changes in wellbore temperature and pressure, can all cause cracks or micro-gaps in the cement sheath, leading to cement sheath isolation failure and affecting wellbore integrity. In recent years, with the increased development of shale gas wells, gas storage wells, carbon storage wells, and fracturing wells, cement sheath integrity has become a research hotspot both domestically and internationally. Existing technical measures include: adding anti-gas channeling agents (such as latex, microsilica, aluminum powder, etc.) to the cement slurry to enhance its resistance to channeling during setting; and adding elastoplastic particles (such as tire powder, polypropylene powder, nitrile rubber powder, etc.) and short fibers (such as acicular wollastonite, carbon fiber, glass fiber, etc.) to the cement slurry to enhance the cement sheath's resistance to stress damage during subsequent oil well production. However, existing technical measures have certain limitations or imperfections. For example, aluminum powder can enhance the cement paste's resistance to cross-contamination and prevent the formation of micro-gaps. However, aluminum powder is prone to premature gas generation (producing hydrogen gas), posing a safety hazard to on-site mixing. In application, the amount of aluminum powder added is small, requiring dry mixing with cement, which can easily lead to uneven mixing. Another example is elasto-plastic particles, which can reduce the brittleness of cement paste. However, while reducing brittleness, they also have a significant negative impact on the strength of cement paste. In application, elasto-plastic particles need to be dry-mixed with cement and occupy limited storage tanks on offshore platforms, causing inconvenience to production scheduling when usage is not at full capacity.

[0003] In addition, existing technologies also employ epoxy resin-modified cement slurry, with the following variations: modification using epoxy resin emulsions without curing agents (e.g., Yan Peiyu et al., Bulletin of the Chinese Ceramic Society, 2016, Vol. 35, No. 7); modification using epoxy resin emulsions and water-based curing agents (e.g., Liu Yuliang et al., Bulletin of the Chinese Ceramic Society, 2019, Vol. 38, No. 2); modification using epoxy resins with hydrophilic groups and curing agents to form a resin solution (e.g., Guo Yuanyao et al., Oilfield Chemistry, 2020, Vol. 37, No. 4); and modification using nonionic emulsifiers (Tween). 80) Modification is achieved by emulsifying a resin solution composed of bisphenol A epoxy resin (E44) and an amide curing agent (polyamide 910) (e.g., Yu Bin et al., Drilling Fluids and Completion Fluids, 2022, Vol. 39, No. 4); modification is also achieved by dispersing a resin solution composed of bisphenol A epoxy resin, diluent, aromatic amine curing agent, and tertiary amine accelerator using a compatibilizer (e.g., US Patent US20180215988 uses polyethyleneimine as a compatibilizer, and US Patent US20170335168 uses a lignite-grafted water-soluble polymer as a compatibilizer). Although epoxy resin modification of cement stone helps maintain its long-term integrity by reducing its permeability and improving its mechanical properties, there are still some shortcomings or areas for improvement in existing epoxy resin modification technologies. For example, the operating temperature range needs to be further broadened, the compatibility between the resin solution and cement slurry needs to be improved, and the shrinkage of the cured resin cement stone needs to be addressed. Summary of the Invention

[0004] The purpose of this invention is to provide a resin cement slurry for cementing, its preparation method, and its application. This technology can be used to solve the problem of long-term integrity of cement sheaths, which is currently a concern in the industry.

[0005] To achieve the objectives of this invention, the technical solution is as follows:

[0006] In a first aspect, the present invention provides a resin cement slurry for cementing, comprising: a resin slurry and a cement slurry in a volume ratio of 0.5:9.5 to 9.5:0.5.

[0007] The above-mentioned resin cement slurry for cementing has a volume ratio of resin slurry to cement slurry of 0.5:9.5 to 4.5:5.5.

[0008] The above-mentioned cementing resin slurry, by weight, comprises 60-100 parts epoxy resin, 0-40 parts diluent, 25-40 parts curing agent, 0.1-2 parts suspending agent, 0.1-0.5 parts aluminum powder, and 0-6 parts accelerator.

[0009] The aforementioned resin cement slurry for cementing includes an epoxy resin that is bisphenol A, bisphenol F, phenolic resin, or an epoxy resin containing hydrophilic groups; a diluent that is an active diluent with mono- or poly-epoxy functional groups; a curing agent that is an aliphatic amine or aromatic amine curing agent; a suspending agent that is an organoclay; a accelerator that is a tertiary amine accelerator; and aluminum powder that is aluminum powder for metallic paint with a particle size of 5–15 μm.

[0010] The aforementioned cementitious slurry for cementing has an epoxy resin viscosity of 2000–15000 cps at room temperature and an epoxy equivalent of 150–200 g / eq.

[0011] The above-mentioned cementing resin slurry has a diluent with a viscosity of 20-100 cps at room temperature and an epoxy equivalent of 100-300 g / eq.

[0012] In the above-mentioned cementing resin slurry, the curing agent is one or more of diethyltoluenediamine and dimethylthiotoluenediamine.

[0013] In the above-mentioned cementing resin slurry, the suspending agent is organically modified sepiolite.

[0014] In the above-mentioned cementing resin slurry, the aluminum powder is a silica-coated aluminum powder used in metallic paints with a particle size of 5-15 μm.

[0015] In the above-mentioned cementing resin slurry, the accelerator is one or more of dimethylaniline, benzyl dimethylamine, and DMP-30.

[0016] The aforementioned cement slurry for cementing is a commonly used cement slurry for cementing containing a compatibilizer.

[0017] The aforementioned cementing resin slurry contains AMPS-type polymer fluid loss reducing agents.

[0018] The compatibilizer in the above-mentioned cementing resin slurry is an alcohol ether sulfate emulsifier with anionic and nonionic structural characteristics, wherein the nonionic structural unit is a polyoxyethylene ether structure and the anionic structural unit is a sodium or ammonium salt of sulfate; in the polyoxyethylene ether structure, the number of repetitions (i.e., EO number) of the hydrophilic part of the ethoxy segment is not less than 15, and the lipophilic part can be an isomeric alcohol, or an alkylphenol, or triphenylethylphenol.

[0019] Secondly, the present invention provides a method for preparing resin cement slurry for cementing, comprising:

[0020] (1) Prepare resin slurry and cement slurry separately;

[0021] (2) Add the resin slurry to the cement slurry according to the proportion, stir and mix to obtain the resin cement slurry for cementing.

[0022] Thirdly, the present invention also provides the application of the above-mentioned resin cement slurry for cementing in oilfield cementing.

[0023] The technical solution of the present invention has the following beneficial effects:

[0024] (1) This invention mixes an oily resin slurry containing aluminum powder with an aqueous cement slurry in a certain volume ratio and uses a compatibilizer in the cement slurry to achieve “in situ emulsification” of the resin slurry in the cement slurry. The operation process is simple and can be carried out on site using existing equipment.

[0025] (2) The resin cement slurry technology provided by the present invention meets the basic performance requirements of cement slurry for cementing engineering, such as thickening adjustability and rheological properties.

[0026] (3) Compared with existing resin modification technologies, this invention improves the compatibility between resin slurry and cement slurry by using alcohol ether sulfate compatibilizers, epoxy resins containing hydrophilic groups, or a combination of the two, thus preventing the separation of resin liquid and cement slurry; by using a combination of aromatic amine curing agents and tertiary amine accelerators, the application temperature range of resin cement slurry is widened to 40-130℃; by using alcohol ether sulfate compatibilizers, epoxy resins containing hydrophilic groups, or a combination of the two, the compatibility between resin liquid and cement slurry is improved, thus preventing the separation of resin and cement slurry; aluminum powder gas generator is added to the resin liquid, and then the resin slurry containing aluminum powder is added to the cement slurry, which facilitates the application of aluminum powder anti-gas channeling agent, and at the same time, the aluminum powder gas generator effectively compensates for the shrinkage of epoxy resin cement slurry during the curing process.

[0027] (4) In this invention, resin is embedded in the cement stone body in the form of micro-nano-sized particles. The resin particles and the surrounding cement body have chemical bonds at the interface due to epoxy ring-opening reaction. Therefore, compared with the prior art of toughening cement stone with elasto-plastic particles, it has advantages. The micro-nano-sized resin particles toughening cement stone has little negative impact on the strength of cement stone and has obvious advantages in interface bonding and oil contamination resistance. Attached Figure Description

[0028] Various other advantages and benefits will become apparent to those skilled in the art upon reading the following detailed description of preferred embodiments. The accompanying drawings are for illustrative purposes only and are not intended to limit the invention.

[0029] Figure 1 and Figure 2 The thickening curves of resin cement slurry No. 2 at 70℃ and 90℃ are shown respectively.

[0030] Figure 3Stress-strain curves of the cured bodies of resin cement slurry No. 2, cement slurry No. 1, and cement slurry obtained by adding 10% (bowc) nitrile particles to cement slurry No. 1.

[0031] Figure 4 and Figure 5 The images show the microstructures of the cured resin cement slurry, numbered 2# and 6#, respectively. Detailed Implementation

[0032] To fully understand the purpose, features, and effects of this invention, the following detailed embodiments are provided. Except as described below, the process methods of this invention employ conventional methods or apparatus in the art. Unless otherwise specified, the terms and expressions used below have the meanings commonly understood by those skilled in the art.

[0033] In the following embodiments, the cement, admixtures and additives involved are all from Blue Ocean Boda Technology Co., Ltd.; the resin cement slurry materials involved are detailed in Table 1; the emulsifiers or compatibilizers involved are detailed in Table 2.

[0034] Table 1 Summary of Resin Cement Slurry

[0035]

[0036] Table 2 Summary of Cement Grout Materials

[0037]

[0038] Example 1

[0039] This embodiment examines the preparation, rheological properties, and stability of resin cement slurry, as shown in Table 3. The resin cement slurry is prepared by adding the prepared resin slurry to the prepared cement slurry and then simply stirring. The formula for cement slurry #1 is: "100% cement + 3.0% G80L + 1.0% F45L + 0.2% X60L + 40% fresh water, 1.90 g / cm³". 3 The formula for #2 cement slurry is: 100% silica fume cement + 3.0% G80L + 1.0% F45L + 0.2% X60L + 40% fresh water, 1.90 g / cm³. 3 (G80L is an AMPS-based polymer desiccant, F45L is a polycarboxylic acid dispersant, X60L is a tributyl phosphate defoamer, and silica fume cement is cement with 30% silica fume); the formula for No. 1 resin slurry is: "NPEL-128 70 parts + GE-11 10 parts + GE-22 20 parts + DETDA 30 parts + Garamite1958 0.5 parts + AL-2 0.5 parts, 1.1 g / cm³ 3The formula for resin slurry #2 is: "70 parts E51C + 10 parts GE-11 + 20 parts GE-22 + 30 parts DETDA + 0.5 parts Garamite 1958 + 0.5 parts AL-2, 1.1 g / cm³". 3 ".

[0040] One of the technical challenges of resin cement slurry is preventing the resin slurry from floating at high temperatures. To prevent this, a certain amount of compatibilizer is usually added to the slurry. In this invention, alcohol ether sulfate (e.g., NPS25) is selected as the compatibilizer, and its dosage is 1 to 3 parts per 100 parts of resin solution (by weight of Resin, bwoR). A comparison is made with existing technical solutions.

[0041] The stability of the resin slurry was investigated at room temperature, 70°C, and 130°C, and the results are shown in Table 3. Table 3 shows that using NPS25 as the emulsifier (see numbers 1# to 4#) alone, the resin-cement slurry prepared with different mixing ratios of resin #1 and cement slurry #1 did not separate at room temperature and 70°C; the resin-cement slurry prepared with NPS25 as the emulsifier and using resin slurry #2 did not separate at 130°C. The rheological values ​​reflected by the viscometer readings indicate that the resin-cement slurry of this invention can meet the requirements for cementing pumping. Comparative Examples 1# to 3# used nonionic emulsifiers, cationic emulsifiers, and amphoteric emulsifiers, respectively, while Comparative Examples 4# to 5# used polyethyleneimine and grafted modified polymers as compatibilizers in the prior art, respectively. None of these methods achieved satisfactory results in preventing resin slurry floating.

[0042] Table 3 Summary of cement slurry stability at different temperatures

[0043]

[0044]

[0045] Note: The symbol " / " in the table means "untested"; the symbol "bwoR" is an abbreviation for "by weight of Resin".

[0046] Example 2

[0047] This embodiment examines the gas generation of aluminum powder in cement slurry. It is well known in the industry that aluminum powder generates hydrogen gas in alkaline cement slurry, which can compensate for the shrinkage that occurs during the curing process of the cement slurry and is beneficial for preventing cross-contamination and the formation of micro-gaps in the cement ring during the setting process. Premature gas generation of aluminum powder poses safety hazards to on-site mixing and also affects the application effect. Therefore, delaying the gas generation of aluminum powder is crucial for its use. Cement slurry containing aluminum powder was placed in a stoppered conical flask, which was then placed in a 40°C water bath to simulate the on-site mixing temperature. The hydrogen gas generated in the conical flask was collected and monitored using the "drainage method," and the results are shown in Table 4. As can be seen from Table 4, aluminum powder immediately generates gas in cement slurry #1. However, when aluminum powder is added to resin liquid, and then the resin liquid containing aluminum powder is mixed with cement slurry, the gas generation of aluminum powder in the resin-cement slurry is significantly delayed. Furthermore, the gas generation of aluminum powder AL-2 coated with silica is further delayed. This delayed gas generation of aluminum powder ensures the safety of on-site mixing.

[0048] Table 4 Summary of Cement Grout Gas Generation Status

[0049]

[0050]

[0051] Example 3

[0052] This embodiment examines the thickening adjustability of resin cement slurry. Resin cement slurry belongs to a "dual-curing" system, meaning the cement curing reaction in the cement slurry and the resin curing reaction in the resin slurry do not interfere with each other. Cement curing can be adjusted using cement retarder, while resin curing is adjusted by different active curing agents and accelerators. In resin cement slurry where cement slurry is dominant (i.e., V...), 树脂浆液 / V 水泥浆 The ratio of cement slurry to resin solution is 9.5:0.5 to 5.5:4.5. Therefore, when the retarder H40L content is 1.0%, thickening tests were conducted on resin-cement slurry (sample #2) at 70℃ and 90℃. The resulting thickening curves were normal, as shown below. Figure 1 and Figure 2 .

[0053] Example 4

[0054] This embodiment investigates the mechanical properties of cured cement slurry. Resin-modified cement slurry #2, cement slurry #1 (reference), and cement slurry obtained by adding 10% (bowc) nitrile butadiene particles to cement slurry #1 (elastomer modified) were selected from Table 1. After curing at 50℃ in a water bath under normal pressure for 7 days, stress-strain curves and mechanical parameters of each cured cement slurry were obtained using a rigidity testing machine. The results are shown below. Figure 3 See Table 5.

[0055] As shown in Table 5, compared to the reference cement slurry cured body, the uniaxial compressive strength and elastic modulus of the resin-modified and elastomer-modified cement slurry cured bodies were both reduced. In the toughening modification of cement sheaths, a higher strength-to-modulus ratio is considered to maintain compressive strength better and is more beneficial for reducing brittleness and toughening the cement paste. Therefore, resin modification is superior to elastomer modification. Furthermore, from... Figure 3 The stress-strain curves of the three types of cement slurry cured bodies show that the resin cement slurry cured body has a clear plastic segment after the peak during the compression process. Based on this, it can be further explained that resin modification is superior to elastomer modification.

[0056] Table 5. Results of mechanical properties of cement slurry solidified body

[0057]

[0058] Example 5

[0059] This embodiment investigates the microstructure of the cured resin cement slurry. Resin cement slurries numbered 2# and 6# in Table 1 were selected and cured at 50℃ under normal pressure for 7 days. The micromorphology of the fresh cross-section of the cured slurry was observed using an S-4700 field emission scanning electron microscope (Hitachi). See [Figure Number]. Figure 4-5 . Figure 4 The image shows the microstructure of the solidified resin cement slurry #2, which reveals that the resin is embedded in the cement stone body as spherical particles of about 20 micrometers in size. Figure 5 The microstructure of the solidified 6# resin cement slurry makes it difficult to detect the presence of micron-sized resin particles. The resin may be embedded in the cement stone body as micro- and nano-sized particles.

[0060] The present invention has been disclosed above with reference to preferred embodiments. However, those skilled in the art should understand that these embodiments are merely illustrative of the invention and should not be construed as limiting its scope. It should be noted that any variations and substitutions equivalent to these embodiments should be considered to be covered within the scope of the claims. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.

Claims

1. A resin cement slurry for cementing wells, characterized in that, include: The volume ratio of resin slurry to cement slurry is 0.5:9.5 to 9.5:0.5; The resin slurry, by weight, comprises 60-100 parts epoxy resin, 0-40 parts diluent, 25-40 parts curing agent, 0.1-2 parts suspending agent, 0.1-0.5 parts aluminum powder, and 0-6 parts accelerator. Wherein, the cement slurry is a commonly used cement slurry for cementing wells containing a compatibilizer; the epoxy resin is a hydrophilic modified bisphenol A type epoxy resin; the curing agent is a fatty amine or aromatic amine curing agent; the suspending agent is an organic clay; and the accelerator is a tertiary amine accelerator. The aluminum powder is a silica-coated aluminum powder for metallic paint with a particle size of 5-15 μm; the compatibilizer is an alcohol ether sulfate emulsifier with anionic and nonionic structural characteristics, wherein the nonionic structural unit is a polyoxyethylene ether structure and the anionic structural unit is a sodium or ammonium salt of sulfate; in the polyoxyethylene ether structure, the number of repetitions of the hydrophilic part of the ethoxy chain segment is not less than 15, and the lipophilic part is an isomeric alcohol or alkylphenol or triphenylethylphenol.

2. The resin cement slurry for cementing according to claim 1, characterized in that, The volume ratio of the resin slurry to the cement slurry is from 0.5:9.5 to 4.5:5.

5.

3. The resin cement slurry for cementing according to claim 1, characterized in that, The diluent is an active diluent having single or multiple epoxy functional groups.

4. The resin cement slurry for cementing according to claim 1, characterized in that, The epoxy resin has a viscosity of 2000–15000 cps at room temperature and an epoxy equivalent of 150–200 g / eq.

5. The resin cement slurry for cementing according to claim 1, characterized in that, The viscosity of the diluent at room temperature is 20–100 cps, and the epoxy equivalent is 100–300 g / eq.

6. The resin cement slurry for cementing according to claim 1, characterized in that, The curing agent is one or both of diethyltoluenediamine and dimethylthiotoluenediamine.

7. The resin cement slurry for cementing according to claim 1, characterized in that, The suspending agent is organically modified sepiolite.

8. The resin cement slurry for cementing according to claim 1, characterized in that, The accelerator is one or more of dimethylaniline, benzyldimethylamine, and DMP-30.

9. The resin cement slurry for cementing according to claim 1, characterized in that, The cement slurry commonly used in well cementing contains AMPS-type polymer fluid loss reducing agents.

10. The method for preparing resin cement slurry for cementing according to any one of claims 1 to 9, characterized in that, include: (1) Prepare resin slurry and cement slurry separately; (2) Add the resin slurry to the cement slurry according to the proportion, stir and mix to obtain the resin cement slurry for cementing.

11. The application of the resin cement slurry for cementing according to any one of claims 1 to 9 in oilfield cementing.

Citation Information

Patent Citations

  • Additive for Improving Homogeneity of Epoxy Resin and Cement Composites

    US20170335168A1

  • Compatibilized Resin-Cement Composite Compositions

    US20180215988A1

  • Cement foaming agent for well cementation of oil-gas well and preparation method thereof

    CN1046150A

  • High-strength low-elasticity water soluble resin cement paste system and application thereof

    CN109504356A